The well-travelled musician : John Sigismond Cousser and musical exchange in Baroque Europe - Owens, Samantha (Music in Britain, 1600-2000., 2017)
John Sigismond Cousser, as performer and composer, was a pioneering figure in the musical history of the European Baroque era.